Coxiella burnetii in Dromedary Camels (Camelus dromedarius): A Possible Threat for Humans and Livestock in North Africa and the Near and Middle East? - Devaux, Christian A.; Osman, Ikram Omar; Million, Matthieu; Raoult, Didier (Frontiers in Veterinary Science, 2020)
The “One Health” concept recognizes that human health is connected to animal health and to the ecosystems. Coxiella burnetii-induced human Q fever is one of the most widespread neglected zoonosis. In the human ecosystems, the main reported reservoirs of C. burnetii are domesticated ruminants, primarily goats, sheep and cattle. Although studies are still too sparse to draw definitive conclusions, the most recent C. burnetii serosurvey studies conducted in herds and farms in Africa, North Africa, Arabian peninsula, and Asia, highlighted that seroprevalence was strikingly higher in dromedary camels (Camelus dromedarius), than in other ruminants. The C. burnetii seroprevalence in camel herds can reach more than 60% in Egypt, Saudi Arabia and Sudan, and 70% to 80% in Algeria and Chad, respectively. The highest seroprevalence was in female camels with a previous history of abortion. Moreover, C. burnetii infection was also reported in ticks of the Hyalomma dromedarii and Hyalomma impeltatum species collected on camels. Even if dromedary camels represent less than 3% of the domesticated ruminants in the countries of the Mediterranean basin Southern coast, these animals play a major socio-economic roles for millions of people who live in the semi-dry and arid zones of Africa, Middle East and Asia. In countries exporting camels, their percentage reaches about 7% and 21% of domesticated ruminants in Chad and Somalia, respectively. To meet the growing consumers demand of camel meat and milk (more than 5 million tons/year of both raw and pasteurized milk) sustained by a rapid increase of population (growth rate 2.26 to 3.76 per year in North Africa), dromedary camels breeding tends to increase from the Maghreb to the Arabic countries. Due to possible long-term storage of C. burnetii in camel hump adipocytes, this pathogen could represent a threat for herds and breeding farms and ultimately for public health. Because this review highlights an hyperendemia of C. burnetii in dromedary camels, a proper screening of herds and breeding farms for C. burnetii is urgently needed in countries where camels breeding is on the rise. Moreover, the risk of C. burnetii transmission from camel to human should be further evaluated.